SOSIALISASI PEMBERIAN MAKANAN BERGIZI PENDAMPING ASI PADA IBU BAYI SEBAGAI INTERVENSI UNTUK MENURUNKAN PREVALENSI STUNTING DI DESA DOREBARA - Astika, Reni; Rachmatullah, Reza; Farid, Muhammad Jailul Qurani; Adhiyasa, I Kadek Wisnu; Fachreza, Muhammad Rafli; Halimatuzzakrah, Halimatuzzakrah; Hidayanti, Silpiya; Rismiyati, Rismiyati; Rachmani, Dyah Fitri; Misbahuddin, Misbahuddin (Universitas Mataram, 2023)
This article discusses intervention efforts to address stunting in Dorebara Village, Dompu Regency, through the Community Empowerment Real Work Lecture (KKN PMD) program by Universitas Mataram. The program involves the dissemination of information about the risks of stunting and the Practice of Clean and Healthy Living (PHBS), the provision of Complementary Feeding (MPASI) in the form of